The Effects of Rice Husk Particles Size as A Reinforcement Component on Resin-Based Brake Pad Performance: From Literature Review on the Use of Agricultural Waste as A Reinforcement Material, Chemical Polymerization Reaction of Epoxy Resin, to Experiments - Asep Bayu Dani Nandiyanto; Siti Nur Hofifah; Gabriela Chelvina Santiuly Girsang; Silmi Ridwan Putri; Bentang Arief Budiman; Farid Triawan; Abdulkareem Sh. Mahdi Al-Obaidi (Automotive Experiences, 2021)
This study aims to investigate the effect of rice husks’ particle size on resin-based brake pad performance (i.e. compressive strength, puncture strength, mass loss, wear rate, friction coefficient, and heat resistance). Bisphenol A-epichlorohydrin and cycloaliphatic amine were mixed to form resin and used as the brake pad's base material. In the experiment, rice husk with a specific particle size (i.e., 250, 500, dan 1000 Î¼m) was added to the resin. Rice husk has received considerable interest due to its lignin, cellulose, and silica content, making it suitable as friction material due to its ceramic-like behavior. The experimental results showed small rice husk particles improved compressive strength, puncture strength, and bulk density. This can be obtained from the analysis of the maximum compressive strength for brake pad supported by particles with sizes of 250, 500, and 1000 Î¼m having values of 0.238; 0.173; and 0.144 MPa, respectively. In contrast, large particles formed coarse surfaces and pores, decreased mass loss rate, and improve friction properties (i.e. wear rate, friction coefficient). The friction coefficient values of brake pad supported by particles with sizes of 250, 500, and 1000 Âµm were, respectively, 0.2075; 0.2070; and 0.3379. Particle size affected interpacking, interfacial bonding, pores number and size, thermal softening, mechanical properties, and friction properties of the brake pad. Comparison between the prepared resin-based and commercial brake pad was also done, confirming the utilization of agro-waste as a potential alternative for friction material in the brake pad.